BÂJÂNG KERTÈ: SENI PERTUNJUKAN WAYANG TOPENG MASYARAKAT SITUBONDO - Hidayatullah, Panakajaya (Dance and Theatre Review, 2025)
This research seeks to examine the bâjâng kertè art form from various aspects, including its history and developmental dynamics, form and function, transmission and regeneration, as well as performance modes and survival strategies. The study employs a qualitative research approach, utilizing ethnographic methods. Data were collected through participatory observation, interviews, and literature review. The data were then interpreted by employing a multidisciplinary perspective, including history and performing arts. The findings reveal that bâjâng kertè is an intangible cultural heritage of significant value to the community of Situbondo. It was created by a skilled Madurese puppeteer named Kertisuwignyo, who later migrated and settled in Situbondo. Bâjâng kertè flourished in Situbondo during the 1970s to the 1990s. It was performed in various contexts such as parlo, rokat panhâbâ, rokat tasè’, rokat bhumi, salamettan, and other events. Its performance structure consists of several parts, including dhing-ghendhingan, tèmangan, tari srimpi, and maen carèta. This art form serves multiple functions within the community, including educational, entertainment, spiritual, and economic purposes. The knowledge and skills related to bâjâng kertè are culturally transmitted by its artists through two pathways: informal learning (cantrik) and group training. Various challenges and problems faced by bâjâng kertè artists have ultimately sparked new innovations. These include the emergence of new performance modes such as topeng rokatan, topeng can-macanan, topeng lawak, and the incorporation of bâjâng kertè content in audiovisual recordings.